PENGARUH SISTEM INFORMASI MANAJEMEN TERHADAP KEPUASAN MASYARAKAT PADA DINAS KOMUNIKASI DAN INFORMATIKA DI PUSAT PEMERINTAKOTA TANGERANG - Diana Sutami; Yusmedi Yusuf; Hilman . (JURNAL ILMIAH ILMU ADMINISTRASI, 2019)
This research is motivated by the importance of the main task and the special role of the communication and informatics center in the field of service and delivery of information for the people of the city of Tangerang. The communication and information technology center of the city government of Tangerang always strives to satisfy its people in creative and innovative ways. The purpose of this study was to determine the effect of management information systems on community satisfaction. The type of research that researchers use is quantitative research using sampling techniques that are accidental sampling techniques. Based on the results obtained in this study between management information systems and community satisfaction has a positive and significant influence on results obtained in the management information systems variable that is equal to 81% of the criteria set and the results obtained on the community satisfaction variable that is equal to 86% of the criteria set.Keywords: Management Information Systems and Community Satisfaction